Insomnia identity. (October 2017) - Lichstein, Kenneth L.
Abstract: Insomnia identity refers to the conviction that one has insomnia, and this sleep complaint can be measured independently of sleep. Conventional wisdom predicts that sleep complaints are synchronous with poor sleep, but crossing the presence or absence of poor sleep with the presence or absence of insomnia identity reveals incongruity with expected patterns. This review of existing research on insomnia identity processes and influence finds that about one-fourth of the population are uncoupled sleepers, meaning there is an uncoupling of sleep and sleep appraisal, and daytime impairment accrues more strongly to those who endorse an insomnia identity. Research supports the conclusion that there is a cost to pathologizing sleep. Individuals claiming an insomnia identity, regardless of sleep status, are at greater risk for a range of sequelae including self-stigma, depression, suicidal ideation, anxiety, hypertension, and fatigue. A broad research agenda is proposed with hypotheses about the sources, clinical mechanisms, and clinical management of insomnia identity. Highlights: Insomnia identity is comprised of the conviction that one has insomnia. Insomnia identity can be uncoupled from sleep resulting in complaining good sleepers and noncomplaining poor sleepers. Insomnia identity is more predictive of daytime impairment than poor sleep. Insomnia identity may impede treatment responsivity and instigate recurrence.